Of Packs & Lone Wolves: Interview with Ellis Amdur Regarding Japanese Martial Traditions, by Peter Hobart - Peter Hobart (Revista de Artes Marciales Asiáticas, 2012)
There are some significant differences in the manner that the classical Japanese martial arts are practiced in the East and in the West. Among these are the student-teacher relationship, the degree of formality and the level of emphasis on etiquette in the dojo. In this interview, noted martial arts teacher Ellis Amdur, who spent thirteen of his more than forty years of martial practice studying in Japan, explores these and other concepts, vital to anyone who wishes to understand the way these arts are (or were) taught in the country of their origin. He also discusses the two particular martial systems (koryu) which he is licensed to teach: Araki-ryu, a rugged system that emphasizes close combat; and Toda-ha Buko-ryu, a system specializing in the use of the naginata against a variety of weapons.